2012
DOI: 10.1523/jneurosci.0752-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Presynaptic Scaffold CAST Reduces Active Zone Size in Rod Photoreceptors and Impairs Visual Processing

Abstract: How size and shape of presynaptic active zones are regulated at the molecular level has remained elusive. Here we provide insight from studying rod photoreceptor ribbon-type active zones after disruption of CAST/ERC2, one of the cytomatrix of the active zone (CAZ) proteins. Rod photoreceptors were present in normal numbers, and the a-wave of the electroretinogram (ERG)-reflecting their physiological population response-was unchanged in CAST knock-out (CAST Ϫ/Ϫ ) mice. Using immunofluorescence and electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
70
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 57 publications
(59 reference statements)
13
70
0
Order By: Relevance
“…However, synaptic ribbons became smaller and lost their “horseshoe”-like shape. We also noticed that a few axonal terminals were located in the photoreceptor nuclear layer, as observed previously in several models of synaptic dysfunction (Liu et al, 2013; Samuel et al, 2014; tom Dieck et al, 2012). Remarkably, we observed no ELFN1 staining in the photoreceptor axonal terminals of TeNT-Cre retinas (Figure 6B).…”
Section: Resultssupporting
confidence: 86%
“…However, synaptic ribbons became smaller and lost their “horseshoe”-like shape. We also noticed that a few axonal terminals were located in the photoreceptor nuclear layer, as observed previously in several models of synaptic dysfunction (Liu et al, 2013; Samuel et al, 2014; tom Dieck et al, 2012). Remarkably, we observed no ELFN1 staining in the photoreceptor axonal terminals of TeNT-Cre retinas (Figure 6B).…”
Section: Resultssupporting
confidence: 86%
“…A third possibility is that presynaptic alterations may lead to decreases in neurotransmitter release that are sensed by postsynaptic partners and lead to their sprouting. Consistent with this model, mutation of several genes implicated in photoreceptor synaptic transmission, including Bassoon and Cacna1f , also lead to sprouting of bipolar and horizontal cells 2427,43,44 . Thus, although loss or delocalization of Bassoon and other structural components of synapses are not detectable in old retina, we speculate that decreased AMPK activity may act in part by decreasing synaptic transmission from rods to their targets.…”
Section: Discussionsupporting
confidence: 52%
“…We examined the effect of ablating these key players on the expression and synaptic targeting of α2δ4. Presynaptically, we found that elimination of the active zone component CAST (tom Dieck et al, 2012), or the synaptogenic molecule ELFN1 (Cao et al, 2015), had no effect on either the abundance or localization of α2δ4 to synaptic ribbons (Fig. 1F).…”
Section: Resultsmentioning
confidence: 94%